Sulphuric Acid-Modified Coal Fly Ash for the Removal of Rhodamine B Dye from Water Environment: Isotherm, Kinetics, and Thermodynamic Studies - G. Bharath Balji; P. Senthil Kumar (Adsorption Science & Technology)
Among the wide variety of dyes present in the environment, cationic dyes are more toxic and have complex structure. The adsorption process of rhodamine B dye was successfully carried out by sulphuric acid-treated inexpensive modified fly ash (MFA) adsorbent via batch experiments. The nature of the adsorbent was characterized by techniques, namely, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). The maximum removal efficiency of RhB dye was found to be 99.78% by using 0.5 g of adsorbent dosage in 50 mg/L of dye concentration. The SEM images displayed the porous nature of the adsorbent where the EDS analysis displays the elemental compositions present in the adsorbent. XRD pattern shows the crystallinity nature of the adsorbent. Among the batch study parameters, effect of pH plays an important role in the adsorption process. The pH of 4 was found to be an ideal setting for the efficient removal of the dye RhB. The preferable elimination ability was found by keeping the dosage at 5 g/L, contact time 120 min, and dye concentration at 50 mg/L. Adsorption capacity was found to be 36.36 mg/g. This shows the ability of the MFA for the removal of wastewater contaminants. This adsorption process is well suited for the Freundlich isotherm, which displaces the process as a multilayer adsorption. Studies in kinetics and thermodynamics demonstrate that the process was well suited for its exothermic nature and pseudo-second-order. Thermal regeneration studies were carried out, and the adsorbent was effectively recycled and utilized up to four more times with minimal loses in its effectiveness. Therefore, from these obtained results, it is clear that the MFA is an effective adsorbent for the effective removal of dyes from wastewater.